Feeding in domestic vertebrates : from structure to behaviour (CABI, 2006)
Domestication of vertebrates is based on the understanding of the needs of animals in their natural environment and the success of this domestication throughout human history is largely dependent on the knowledge of their feeding behaviour. The aim of this volume is to provide advanced students and researchers with a review of current knowledge of feeding in domestic mammals and birds. The first few chapters cover feeding structures and mechanisms in birds and mammals, while the rest of the book presents chapters on feeding behaviour in particular species. The scope is wide, covering not only ruminants, pigs and poultry, but also more specifically horses, rabbits and ostrich. Contributors include leading research workers from Europe, the USA, Australia and South Africa. This book will be of significant interest to researchers in animal physiology and nutrition.